Time course and outcome of central recurrence after radiation therapy for carcinoma of the cervix. Issue 3 (1st April 2006) - Eifel, P. J.; Jhingran, A.; Brown, J.; Levenback, C.; Thames, H.
Abstract : We investigated the time course of central disease recurrence (CDR) in 2997 patients treated with radiation for stage I–II squamous cell carcinoma of the cervix. CDR rates were 6.8%, 7.8%, and 9.6%, at 5, 10, and 20 years, respectively. The risk of CDR was independently correlated with tumor size ( P < 0.0001) but not with FIGO stage. The hazard rate peaked in the first year of follow-up and then fell steeply; after 3 years, the hazard rate was approximately constant at 0.2–0.4% per year. Although after 3 years the risk of CDR was low, it continued to be slightly greater for patients with tumors ≥5 cm than for those with smaller tumors ( P = 0.001). Patients who had CDR <36 months after treatment were less likely to be candidates for salvage therapy and had a poorer postrecurrence survival rate than those with recurrence ≥36 months after treatment (4.5% versus 42.1%, P < 0.0001). The higher rate of CDR in the first 3 years and the poor survival after early recurrence suggest that most early CDRs are true relapses. The relatively stable annual actuarial risk between 3 and 25 years and the better survival rate after late CDR suggest that most "recurrences" after 3 years are actually new neoplasms.